NEW FORMULATIONS OF HYDROCORTISONE-17-BUTYRATE IN THE ARSENAL OF MEANS FOR TOPICAL TREATMENT OF ATOPIC DERMATITIS IN CHILDREN - N. G. Korotkii; B. N. Gamayunov (Вопросы современной педиатрии, 2014)
Topical therapy of atopic dermatitis in children is a complex and multifactorial problem. Irrational choice of means of treatment may lead to the deterioration of the child, cause complications of dermatosis, promote the development of «atopic march». Topical treatment’s «Gold standard» is topical corticosteroids. The application of these medicines is not limited to conventional dosage forms such as cream and ointment. The features of the new formulations are presented (emulsions with different lipid concentration), the recommendations on their practical use are stated, the clinical experience of their application in the treatment of children with atopic dermatitis is described.